Pandangan Orang Tua Dalam Memilih Pendidikan Berbasis Islam (Studi Kasus Pondok Pesantren Syekh Muhammad Arsyad Al-Banjari Balikpapan) - Muhammad Makbul Khoir; Siti Fatimah; erina siskawati (At-Tarbiyah Jurnal Pendidikan,Kebudayaan dan Keislaman, 2025)
This study aimed to explore in depth the views and motivations of parents in choosing Islamic-based education for their children, focusing on Pondok Pesantren Syekh Muhammad Arsyad Al-Banjari in Balikpapan. The background of this research is based on the central role of parents as the primary and first educators for children in the family, especially in facing modern era challenges characterized by rapid technological developments and increasingly complex external environmental influences on children's growth and development. This research used a qualitative approach with a case study method. Data were collected through observation techniques, in-depth interviews, and documentation with parents of students who enrolled their children at Pondok Pesantren Syekh Muhammad Arsyad Al-Banjari Balikpapan. The results showed that parents' motivation in choosing Islamic-based education can be categorized into two main factors, namely intrinsic and extrinsic factors. Intrinsic factors include parents' strong desire to form children’s noble personalities, have Islamic characters, and be able to practice religious teachings in daily life. Meanwhile, extrinsic factors include the religious pesantren environment, the existence of a curriculum integrated with Islamic values, the exemplary role of ustaz and teachers, and the hope that children will be able to face the challenges of the times with strong religious knowledge.